A Functional Hexaphenylbenzene Library Comprising of One, Three, and Six Peripheral Rylene‐Diimide Substituents. Issue 5 (28th December 2020) - Dusold, Carolin; Platzer, Benedikt; Haines, Philipp; Reger, David; Jux, Norbert; Guldi, Dirk. M.; Hirsch, Andreas
Abstract: Synthesis and characterization of a series of rylene‐diimide substituted hexaphenylbenzenes (HPBs) is presented. The direct connection of the rylene‐diimide units to the HPBs via the imide‐ N ‐position without any linkers as well as the use of naphthalene‐diimides (NDIs) next to perylene‐diimides (PDIs) is unprecedented. While mono‐substituted products were obtained by imidization reactions with amino‐HPB and the respective rylene‐monoimides, key step for the formation of tri‐ and hexa‐substituted HPBs is the Co‐catalysed cyclotrimerization. Particular emphasis for physic‐chemical characterization was on to the number of NDIs/PDIs per HPB and the overall substitution patterns. Lastly, Scholl oxidation conditions were applied to all HPB systems to generate the corresponding hexa‐ peri ‐hexabenzocoronenes (HBCs). Importantly, the efficiency of the transformation strongly depends on the number of NDIs/PDIs. While three rylene‐diimide units already hinder the Scholl reaction, the successful synthesis of mono‐substituted HBCs is possible. Abstract : One, three and six rylene‐diimide units, namely NDIs and PDIs, were attached to a HPBs core, generating a unprecedent library of star‐like architectures, which were investigated toward their physicochemical properties. A direct connection between the rylenes and HPB via the imide N ‐position was chosen, rather than using a spacer. Successful Scholl oxidation generates mono‐substituted HBCs as promising donor–acceptor hybrids.